2005
DOI: 10.7326/0003-4819-142-12_part_1-200506210-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Estrogen and Progesterone Hormone Replacement Therapy on Disease Activity in Systemic Lupus Erythematosus: A Randomized Trial

Abstract: Adding a short course of HRT is associated with a small risk for increasing the natural flare rate of lupus. Most of these flares are mild to moderate. The benefits of HRT can be balanced against the risk for flare because HRT did not significantly increase the risk for severe flare compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
393
2
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 588 publications
(419 citation statements)
references
References 37 publications
4
393
2
20
Order By: Relevance
“…A result from our study and the SELENA trial (24) that is worth discussion is that thrombotic events occurred more often and at an identical ratio (3:1) in women receiving menopause hormonal therapy than in those receiving placebo. This result is consistent with results of observational studies (35)(36)(37) and clinical trials (4) of the use of menopause hormonal therapy among healthy women.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A result from our study and the SELENA trial (24) that is worth discussion is that thrombotic events occurred more often and at an identical ratio (3:1) in women receiving menopause hormonal therapy than in those receiving placebo. This result is consistent with results of observational studies (35)(36)(37) and clinical trials (4) of the use of menopause hormonal therapy among healthy women.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, the SELENA group, using the same hormone regimen in postmenopausal women, found that the rate of severe flares and the mean change in the activity index score were not different between women who received menopause hormonal therapy and those who received placebo; nevertheless, women receiving menopause hormonal therapy experienced an increased rate of mild or moderate flares (24). In our study, although the number of patients with flares and the probability of flares tended to be higher among women receiving menopause hormonal therapy, especially when the lupus was active at baseline, the incidence rate of flares was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The subjects included in this trial consisted of 34 women ages 18–50 years with a history of mild to moderate SLE (fulfilling American College of Rheumatology (ACR) criteria for SLE) with minimally active or inactive disease who consented and completed the study. 38-40 This phase I study was approved by the Human Investigation Committee and Institutional Review Board (IRB #051012PH1F) at Wayne State University and the U.S. Food & Drug Administration (FDA) under investigational new drug (IND) application BB14113 for Gardasil® (Merck & Co., Inc.) with a local Data Safety Monitoring Board (DSMB) to monitor the study. This small sample size was determined as adequate by the FDA and Merck scientific team as an initial study to assess safety and immunogenicity in this high risk autoimmune population.…”
Section: Methodsmentioning
confidence: 99%
“…Each pair was assigned to use 1 of the 3 flare assessment instruments: the BILAG 2004 index 12 (6 pairs), the SFI 13 (6 pairs), and the rSFI 9 (6 pairs). Full details of the flare instruments are shown in Supplementary Appendices [Link], [Link], [Link], [Link], [Link] (available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.23252/abstract).…”
Section: Methodsmentioning
confidence: 99%